If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 5 = 8x + -9 Reorder the terms: 5 + 5x = 8x + -9 Reorder the terms: 5 + 5x = -9 + 8x Solving 5 + 5x = -9 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 5 + 5x + -8x = -9 + 8x + -8x Combine like terms: 5x + -8x = -3x 5 + -3x = -9 + 8x + -8x Combine like terms: 8x + -8x = 0 5 + -3x = -9 + 0 5 + -3x = -9 Add '-5' to each side of the equation. 5 + -5 + -3x = -9 + -5 Combine like terms: 5 + -5 = 0 0 + -3x = -9 + -5 -3x = -9 + -5 Combine like terms: -9 + -5 = -14 -3x = -14 Divide each side by '-3'. x = 4.666666667 Simplifying x = 4.666666667
| -5p+5+6p=10 | | Ep+q=29 | | f(x+3)=x^2+5x+3 | | M=-4x+9z-9+2x-2z+4 | | 2(x-5)=3(5x+1) | | 9x-4=52-5x | | x^4-3x^3+4x+1=0 | | B=6x+3a-9+7x-8a+2 | | 4x-7+9x+13-5x-4= | | 6*x+x=63 | | 27=y-11 | | 3/(1-sqr19) | | 7x+17x+3y=180 | | 6(2x+3)=3(6x+4) | | 0/0=1 | | -(x/2) | | 2x-(2x+9)-6=-4x-6(-9-x)+2 | | U=7x+6b-5+2x-6b+4 | | 4y=120 | | (p^5/p^3)^6 | | 12m=9 | | 3x^2+6y^2=18 | | 5x-11=2(x+2) | | J=11-2.5(1.56) | | Z+-4x=2y | | y^3+2x=x-1 | | (8+2i)(5-9i)= | | -36+4x=12 | | 2x+4y-1=3+y | | 8-8x20/20 | | f(x+8)=2x-4 | | x^2+lnx-1=0 |